Structural vulnerability to community victimization and perception of insecurity in young students - Almanza Avendaño, Ariagor Manuel; Gómez SanLuis, Anel Hortensia; Medina Segura, Angel Fernando (Pensando Psicología, 2022)
Objectives: Identify the levels of perception of insecurity and community victimization (direct, indirect and contextual); compare the levels of perception of insecurity according to elements of structural vulnerability (gender, educational level and social class); to analyze the association between types of community victimization with gender, educational level, social class and level of perception of insecurity. Methodology: A comparative and correlational study was carried out with a non-probability sample made up of 310 students (55.8% women and 44.2% men), with an age range of 13 to 24 years, belonging to different educational levels (junior-high school, high-school and college). Results: Moderate levels of perception of insecurity were found, and a predominance of indirect and direct victimization for crimes such as robbery and assault. Contextual victimization is linked to high impact crimes such as homicide and disappearance. Women experience a greater perception of insecurity, direct sexual harassment, and more frequently report sexual violence and disappearance in their community. College level is closer to direct and contextual sexual violence. Belonging to a higher class was associated with direct and indirect victimization for robbery, as well as reporting disappearances in the community more frequently. Conclusions: Gender was the element of structural vulnerability that was most associated with community victimization and the perception of insecurity. A high perception of insecurity is linked to direct victimization, as well as the occurrence of high impact crimes in the community.